DAMPAK KRISIS EKONOMI TERHADAP EKSPOR MINYAK KELAPA SAWIT INDONESIA : ANALISIS SIMULASI JANGKA PANJANG - Harita, Sri; Mawardati, Mawardati; Suryadi, Suryadi (LPPM Universitas Malikussaleh - Indonesia, 2021)
This study aims to analyse the impact of the economic crisis on Indonesia's palm oil exports. This study uses the Two-Stage Least Square (2SLS) method and time series data (2000 - 2018). The results showed that Indonesia's economic growth contracted to 5.32% which led to an economic recession due to the Covid-19 pandemic and the United States-China trade war which caused Indonesia's palm oil exports to decline significantly. However, an increase in domestic palm oil consumption is expected due to lower palm oil prices and the implementation of domestic industrial policies. Under these conditions, the depreciation of the rupiah (11%) and the reduction of palm oil import tariffs from trading partner countries are predicted to improve Indonesia's palm oil export performance, but it is still low on a net basis compared to average economic growth conditions. This proves that a reduction in export tariffs (Indonesia) and import tariffs (trading partner countries) when there is a depreciation of the Rupiah due to a contraction in economic growth is able to improve Indonesia's palm oil export performance